30 years of contemporary hospitality management: Uncovering the bibliometrics and topical trends. Issue 7 (8th July 2019) - Ali, Faizan; Park, Eunhye (Olivia); Kwon, Junehee; Chae, Bongsug (Kevin)
Abstract : Purpose: This paper aims to showcase the trends in the research topics and their contributors over a time period of 30 years in the International Journal of Contemporary Hospitality Management ( IJCHM ). To be specific, this paper uncovers IJCHM 's latent topics and hidden patterns in published research and highlights the differences across three decades and before and after Social Sciences Citation indexing. Design/methodology/approach: In total, 1, 573 documents published over 199 issues of IJCHM were analyzed using two computational tools, i.e. metaknowledge and structural topic modeling (STM), as the basis of the mixed method. STM was used to discover the evolution of topics over time. Moreover, bibliometrics (and network analysis) were used to highlight IJCHM 's top researchers, top-cited references, the geographical networks of the researchers and differences in the collaborative networks. Findings: The number of papers published continually increased over time with changes of key researchers publishing in IJCHM . The co-authorship networks have also changed and revealed an increasing diversity of authorship and collaborations among authors in different countries. Moreover, the variety of topics and the relative weight of each topic have also changed. Research limitations/implications: Based on the findings of this study, theoretical and practical implications for hospitality and tourism researchers are provided. Originality/value: It is the first attempt to apply topic modeling to a leading academic journal in hospitality and tourism and explore the diversity in contemporary hospitality management research (topics and contributors) from 30 years of published research.